KAJIAN HUKUM TERHADAP PENGELOLAAN ASET DAERAH - Basri, Hasan (Jurnal Ilmu Hukum Reusam, 2021)
Regional property (BMD) can be obtained from apbd or other legitimate acquisitions and become regional wealth. State wealth in ministries / institutions / local governments become the authority and responsibility of ministries / institutions / local governments. But in the course of regional asset management sometimes also poses problems. Whereas well-managed regional assets will have a strategic role in supporting regional budget revenues. Bmd utilization applies to BMD located in the user of the goods, as well as who manages the goods. The existence of provisions, ensuring the process of utilization of BMD can run in an orderly, directed, fair, accountable, to realize efficient, effective, and optimal bmd management therefore regional asset management needs to be established and implementation based on the provisions of applicable laws and regulations. There should be a new mindset in the management of state assets so that not only just to record also list its fair value in the government financial report (LKPP), there should also be new thinking on how to optimize the management of state assets to be more optimal. The purpose of this writing is to review from the legal aspects regarding the management of regional assets. The research method used in this writing is done with literature studies. The approach used in this study is the approach of legislation and conceptual approach. The data source in this paper uses secondary legal material in the form of all publications about which are not official documents.